The evaluation of nursing care from the patient perspective - Furtak-Niczyporuk, Marzena; Kos, Marek; Jurek, Anna; Albiniak, Michał (Journal of Education, Health and Sport, 2017)
Introduction: The evaluation of received medical service is seen by the patient as the final stage in the comparison between expectations and reality. Especially when a hospitalised patient has the opportunity to pay closer attention to such elements associated with medical staff as their behaviour, availability, responses to difficult situations, empathy, and support. The evaluation of medical service quality by the patient is, undoubtedly, of great importance to medical entities. The quality of medical services usually constitutes the most vital criterion in selecting a medical facility by the patient. Therefore medical entities have to keep track of the patient’s needs in order to remain competitive. It is the quality of services provided by medical facilities that ensures the patient’s safety and satisfaction, as well as a particular entity’s high position on the medical service market. Aim: This paper aims at illustrating the quality of nursing care as assessed by hospitalised patients. The study was to show the nursing care quality according to the criteria of the evaluation of the medical staff’s work and the attitude towards the provided services. These criteria include kindness, politeness, availability, empathy, gentleness in conducting particular procedures, approach and means of communication. Material and Methods: The study was conducted in a group of 150 patients attending the Independent Public Healthcare Institution in Kraśnik. The public inquiry utilised the diagnostic survey method and the research technique in the form of a poll. The study was performed using author’s questionnaire which included 28 open and closed questions, of which 8 were sociometric in nature and the remaining 20 concerned the evaluation of nurses’ and midwives’ care. The study was performed in the period from January to May 2013. The results and conclusions: The results indicated that the level of nursing care quality provided by the Independent Public Healthcare Institution in Kraśnik was very high. This high grade was confirmed by the satisfaction of nearly 97% of patients who participated in the survey. The most pleased with the services were the respondents hospitalised at the 1 st Internal Diseases and Gastroenterology Ward. The work of the nurses’ team there received very high scores. The lowest score was obtained by the nursing personnel of the General Surgery Ward with Endoscopic Surgery Subdivision. The biggest study group (28 persons) was hospitalised in this ward. The high level of nursing care quality creates huge opportunities to create new marketing strategies concerning a given medical entity. Mainly it creates a very positive image of the place and guarantees the entity’s high position among other medical service providers. But, most importantly, the high quality of medical services increases patients’ safety, which constitute the main indicator of medical entity’s activities.